The Relationship Between Gadget Use And Social Interaction Skills Of Children Aged 5–6 Years At TPP Cahaya Insan Cendekia Kindergarten, Bandar Lampung - Putri Maharani; Gian Fitria Anggraini; Nopiana Nopiana (FKIP UNSULTRA, 2026)
This study aims to determine the relationship between gadget use and social interaction skills of children aged 5–6 years. This research uses a quantitative approach with a correlational design. The sample consisted of 62 children from three classes at TK TPP Cahaya Insan Cendekia. Data were collected using a Likert-scale questionnaire and supported by observation. The results showed that gadget use was in the low category (81%), while children's social interaction skills were in the high category (90%). The Pearson Product Moment correlation test showed a correlation coefficient of –0.302 with a significance value of 0.017 (p < 0.05), indicating a significant relationship between gadget use and children's social interaction skills. Findings of the study confirm that there is a significant negative relationship between the two variables. The study concludes that the relationship is negative, meaning that higher gadget use tends to reduce children's social interaction skills. This indicates that increased exposure to gadgets may contribute to lower social interaction abilities in early childhood. Therefore, proper supervision of gadget use is necessary to support children's social development. Parental and educational control is essential to ensure balanced use of digital technology and optimal social development in children.